Individualized muscle architecture and contractile properties of ankle plantarflexors and dorsiflexors in post-stroke individuals - Wang, Ruoli; Zhang, Longbin; Jalo, Hoor; Tarassova, Olga; Pennati, Gaia Valentina; Arndt, Anton (Frontiers in Bioengineering and Biotechnology, 2024)
Objective: This study was to investigate alterations in contractile properties of the ankle plantar-and dorsiflexors in post-stroke individuals. The correlation between muscle architecture parameters and contractile properties was also evaluated. Methods: Eight post-stroke individuals and eight age-matched healthy subjects participated in the study. Participants were instructed to perform maximal isometric contraction (MVC) of ankle plantar-and dorsiflexors at four ankle angles, and isokinetic concentric contraction at two angular velocities. B-mode ultrasound images of gastrocnemius medialis (GM) and tibialis anterior (TA) were collected simultaneously during the MVC and isokinetic measurements. Individualized torque-angle and torque-angular velocity relations were established by fitting the experimental data using a second-order polynomial and a rectangular hyperbola function, respectively. Muscle structure parameters, such as fascicle length, muscle thickness and pennation angle of the GM and TA muscles were quantified. Results: Poststroke subjects had significantly smaller ankle plantarflexor and dorsiflexor torques. The muscle structure parameters also showed a significant change in the stroke group, but no significant difference was observed in the TA muscle. A narrowed parabolic shape of the ankle PF torquefiber length profile with a lower width span was also found in the stroke group. Conclusion: This study showed that the contractile properties and architecture of ankle muscles in post-stroke individuals undergo considerable changes that may directly contribute to muscle weakness, decreased range of motion, and impaired motion function in individuals after stroke.